(untitled) - Benagh, Christine L. (U.S.A, 1964)
These meditations are set down in the hope that they may shed some light on a superb and joyous surprise hidden in the Book of Job which, so far as I can discover, goes generally unappreciated
Keywords: Bible -- Job -- Meditations